An analysis of the sponge Acanthostrongylophora igens' microbiome yields an actinomycete that produces the natural product manzamine A - Waters, Amanda L.; Peraud, Olivier; Kasanah, Noer; Sims, James W.; Kothalawala, Nuwan; Anderson, Matthew A.; Abbas, Samuel H.; Rao, Karumanchi V.; Jupally, Vijay R.; Kelly, Michelle; Dass, Amala; Hill, Russell T.; et al. (Frontiers in Marine Science, 2014)
Sponges have generated significant interest as a source of bioactive and elaborate secondary metabolites that hold promise for the development of novel therapeutics for the control of an array of human diseases. However, research and development of marine natural products can often be hampered by the difficulty associated with obtaining a stable and sustainable production source. Herein we report the first successful characterization and utilization of the microbiome of a marine invertebrate to identify a sustainable production source for an important natural product scaffold. Through molecular-microbial community analysis, optimization of fermentation conditions and MALDI-MS imaging, we provide the first report of a sponge-associated bacterium (Micromonospora sp.) that produces the manzamine class of antimalarials from the Indo-Pacific sponge Acanthostrongylophora ingens (Thiele, 1899) (Class Demospongiae, Order Haplosclerida, Family Petrosiidae). These findings suggest that a general strategy of analysis of the macroorganism’s microbiome could significantly transform the field of natural products drug discovery by gaining access to not only novel drug leads, but the potential for sustainable production sources and biosynthetic genes at the same time.